Pemetaan Menara Telekomunikasi Kota Denpasar - Sukadarmika, Gede; Linawati, Linawati (Majalah Ilmiah Teknologi Elektro; Vol 12 No 1 (2013): (January - June) Majalah Ilmiah Teknologi Elektro, 2013)
The sharp increase on the demand of mobile telecommunication services requires strategy from providers and government to overcome the need on the mobile network infrastructure. Denpasar is the capital city of Bali Province also as one of the world tourism destination has the dramatic increase in development of mobile telecommunication infrastructure. It can be seen from the number of Greenfield and Rooftop telecommunication tower increase every year. This paper shows the telecommunication tower distribution at Denpasar in year 2012. Survey was done through literature study based on recorded data at the communication and information office at the Government of Denpasar City. In addition, we did the site visit survey to find out the coordinate and tower identities. Then, each towers coordinate was plotted at google map to see the towers distribution and mapping in Denpasar. From the survey and tower mapping we found that there were a number of 326 total telecommunication towers in the area Denpasar. It was consist of 108 unit Greenfield towers and 218 unit Rooftop towers. The site survey also found that many towers have been used by some providers (joint operation tower). There was no tower found located at the Greenland area as well as at the holy and sacred area such as around temples which is very important to be analyzed when planning tower location.  However, many tower were not equipped with the tower identity which has been a requirement base on communication and Information Ministry’s decree number 02/PER/M.KOMINFO/3/2008 about the Guidelines of Joint Operation Telecommunication Tower.
Keywords: Tower, Wireless, Greenfield, Rooftop